Evaluation Study on Construction of Hostels for SC Boys and Girls All India (Report) - Planning Commission (Planning Commission, 2009)
The Centrally Sponsored Scheme (CSS) of construction of new hostels as well as expansion of existing hostels for SC girls was initiated in 1963-64 so as to give an impetus to education of girls belonging to the SC community. During 1989-90, based on the recommendations of the Working Group on the Development and Welfare of SCs and STs, this scheme was extended to SC boys also. The scope of the scheme was enlarged further to cover institutions of higher education/learning such as colleges and universities. The main objective of the CSS is to provide free boarding and lodging facilities in the hostels for SC boys and girls studying at Schools and Colleges/University levels. In order to integrate the SC students with the mainstream, 10 percent of total accommodation in such hostels was left for non-SC students. At the instance of the Ministry of Social Justice and Empowerment, the Programme Evaluation Organisation, Planning Commission, conducted an evaluation study of the scheme in 8 selected states. The study was launched in November, 2004 with the following objectives: (i) To study the approval procedures of the proposals for construction of hostels. (ii) To study the process of implementation of the scheme in various States vis-a-vis the guidelines.
Programme Evaluation Organisation Planning Commission New Delhi